2020
DOI: 10.1519/jsc.0000000000002810
|View full text |Cite
|
Sign up to set email alerts
|

Normative Data and Physical Determinants of Multiple Sprint Sets in Young Soccer Players Aged 11–18 Years: Effect of Maturity Status

Abstract: Selmi, MA, Sassi, RH, Yahmed, MH, Giannini, S, Perroni, F, and Elloumi, M. Normative data and physical determinants of multiple sprint sets in young soccer players aged 11–18 years: Effect of maturity status. J Strength Cond Res 34(2): 506–515, 2020—The aims of the study were: (a) to establish normative data for repeated-sprint sets (RSS) test based on the maturity status (age at peak height velocity [PHV]) and (2) to investigate the relationship between anthropometrical variables (stature, sitting height, bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 39 publications
1
17
0
1
Order By: Relevance
“…Therefore, these outcomes suggest that the speed training should be more specific from the U16 age category onwards. Whereas, the use of RSA protocols for talent identification should be applied once players surpass the peak height velocity period (Perroni et al, 2018b ; Selmi et al, 2018 ). It is important to consider that the characteristics of each repeated-sprint ability test (recovery duration, number of sprints, distance, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, these outcomes suggest that the speed training should be more specific from the U16 age category onwards. Whereas, the use of RSA protocols for talent identification should be applied once players surpass the peak height velocity period (Perroni et al, 2018b ; Selmi et al, 2018 ). It is important to consider that the characteristics of each repeated-sprint ability test (recovery duration, number of sprints, distance, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has pointed out that the repeated sprint ability (RSA) is related to physiological parameters such as maximal oxygen uptake or muscle phosphocreatine degradation/resynthesis among others (Spencer et al, 2005 ). Recent research has reported percentile values of repeated sprint performance of young soccer player classified by maturity status (Selmi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More research to clarify both assumptions is needed. Thereby, in elite junior soccer players, it is important to control for the interindividual variation in the maturity status [9], for example, by peak height velocity measures [42]. Since biological and chronological ages can differ up to four years [43], the different maturation processes may have had an impact on our measures; especially, in our younger age groups.…”
Section: Discussionmentioning
confidence: 99%
“…In soccer, it is accepted that anthropometric characteristics and physical capacities like muscle mass, speed, agility, repeated sprint ability, power, strength, maximum oxygen uptake, and intermittent endurance are important prerequisites to fulfill the playing demands [2,8]. Thus, in soccer, knowledge of anthropometric characteristics and physical capacities is essential to optimize the training process on an individual basis [8], for example, according to the age of the players [9,10]. In elite junior soccer players, it is known that the muscle mass [11,12], repeated sprint ability [13], strength and power [14,15], and speed [3,10,12,14,16,17] capacities increase with maturation and training experience.…”
Section: Introductionmentioning
confidence: 99%